Letter from Robert S. Mulliken to Harrison Shull, 1958 - Mulliken, Robert Sanderson (1958)
Concerns Mulliken's travel plans in Stockholm and Moscow.
Keywords: Shull, Harrison; Mulliken, Robert Sanderson; Chemists